Establishment and characterization of a new human Ph+ erythroleukemic cell line, VES - Golemović, Mirna (Array, 2005)
Continuous human malignant hematopoietic cell lines are invaluable tool for hematological research. Here we report on a new erythroleukemic cell line termed VES that was established from the bone marrow mononuclear cells (BMNC) of a 22-year-old woman with Ph+ chronic myeloid leukemia (CML). During second post-transplant recovery her bone marrow was tested Ph-negative by FISH and PCR and BMNC were introduced into culture. On the day 27 blast-like cells appeared in the supernatant of cell culture. They expressed highly amplified bcr/abl locus as shown by FISH, whereas the patient’ s bone marrow was still Ph-negative at the time. Very soon, the cultured cells started to express stable features of erythroleukemia cell line. Optimal growth was obtained at concentration of 0.3x106 cells/ml in IMDM containing 10% FBS. After 3 days of culture, cell concentration varied between 1.3 and 1.8x106cells/ml. VES cells were tested negative for the presence of EBV. For analysis of clonogenicity, 103cells/ml were grown in a serum-free methylcellulose medium without cytokines. Following 7-day culture, 103 VES cells produced 251&plusmn ; ; ; 42 and after 14 days 431&plusmn ; ; ; 30 GF-independent colonies. On day 14 it was possible to observe reddish color of the colonies indicating the presence of hemoglobin. Cytological examination revealed homogenous population of leukemia blasts (>80%) the majority of them (>90%) being glycophorin A positive and MPO negative. Immunophenotyping indicated proerythroblastic lineage-associated profile: GlyA+, CD11b+, CD15+, CD29+, CD33+ and CD117+. Cytogenetics revealed complex karyotype with multiple numerical/structural abnormalities (MAKA), while metaphase FISH revealed t(9 ; 22), 5q31, 7q31, +8, +6. Since FISH analysis detected highly amplified bcr/abl locus, we tested VES cells’ sensitivity to imatinib (Gleevec, Novartis). Treatment with imatinib for 3 days (MTS assay) inhibited proliferation of VES cells with IC50 value of 0.2 M. Following 14 days of culture in methylcellulose medium with addition of 0.2 M imatinib, the clonogenic potential of VES cells was reduced by 55%. Furthermore, imatinib induced apoptosis in VES cells in time- and dose-dependant manner, assessed by AnnexinV/PI staining. We believe that VES cells represent a suitable model for studying Ph+ malignant hematopoiesis in vitro.